Use of antipsychotics, benzodiazepine derivatives, and dementia medication among older people with intellectual disability and/or autism spectrum disorder and dementia. (March 2017) - Axmon, Anna; Kristensson, Jimmie; Ahlström, Gerd; Midlöv, Patrik
Abstract: Background: Although people with intellectual disability (ID) and people with dementia have high drug prescription rates, there is a lack of studies investigating drug use among those with concurrent diagnoses of ID and dementia. Aim: To investigate the use of antipsychotics, benzodiazepine derivatives, and drugs recommended for dementia treatment (anticholinesterases [AChEIs] and memantine) among people with ID and dementia. Methods and procedures: Having received support available for people with ID and/or autism spectrum disorder (ASD) was used as a proxy for ID. The ID cohort consisted of 7936 individuals, aged at least 55 years in 2012, and the referent cohort of age- and sex-matched people from the general population (gPop). People with a specialists' diagnosis of dementia during 2002–2012 were identified (ID, n = 180; gPop, n = 67), and data on prescription of the investigated drugs during the period 2006–2012 were collected. Outcome and results: People with ID/ASD and dementia were more likely than people with ID/ASD but without dementia to be prescribed antipsychotics (50% vs 39% over the study period; odds ratio (OR) 1.85, 95% confidence interval 1.13–30.3) and benzodiazepine derivatives (55% vs 36%; OR 2.42, 1.48–3.98). They were also more likely than people with dementia from the general population to be prescribed antipsychotics (50% vs 25%; OR 3.18, 1.59–6.34), but less likely to be prescribed AChEIs (28% vs 45%; OR 0.32, 0.16–0.64).